2002
DOI: 10.1097/00006676-200207000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Elastase 1 Measurement Compared with Endoscopic Retrograde Cholangiopancreatography for the Diagnosis of Chronic Pancreatitis

Abstract: Fecal elastase 1 measurements appear to be valuable for characterizing patients at high risk for chronic pancreatitis, even if their sensitivity is lower than that of direct tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The specificity was reported to be around 90% [30,31]. Comparing FEC to ERCP images, there was a good specificity for pathological pancreatic duct changes [32]. Fecal elastase 1 [33].…”
Section: Discussionmentioning
confidence: 99%
“…The specificity was reported to be around 90% [30,31]. Comparing FEC to ERCP images, there was a good specificity for pathological pancreatic duct changes [32]. Fecal elastase 1 [33].…”
Section: Discussionmentioning
confidence: 99%
“…To date, two commercially available enzyme-linked immunosorbent assays (ELISAs) have been used for the measurement of FE-1, by means of a monoclonal or polyclonal antibody. The monoclonal FE-1 assay has been confirmed to have good sensitivity and specificity for moderate and severe PEI in comparison with direct function tests, as well as with magnetic resonance cholangiopancreatography (MRCP) combined with diffusion-weighted magnetic resonance imaging (MRI) and endoscopic retrograde cholangiopancreatography (ERCP), which was long regarded as the gold standard of pancreatic imaging for CP [23][24][25][26][27]. More recently, a polyclonal FE-1 assay has been developed using two different polyclonal antisera to human pancreatic elastase, which recognize different antigenic epitopes [28].…”
Section: The Fecal Elastase-1 Testmentioning
confidence: 99%
“…112 Vice versa, Hardt et al observed that pathological faecal elastase-1 concentrations at a cutoff point of 200 mg/g had a positive predictive value of more than 95% for pancreatic duct alterations in more than 200 patients undergoing endoscopic retrograde cholangiopancreatography (ERCP), though sensitivity of elastase-1 measurements was low (45%). 137 In addition, comparison of the results of the secretin test with ERP findings in 192 chronic pancreatitis patients revealed parallel results in about 75%, whereas impairment of exocrine function and morphologic alterations did not occur in parallel in about 25%, predominantly in patients with non-calcifying chronic pancreatitis 136 Similarly, Lankisch et al observed parallel SC test and ERCP findings in 64% of 202 chronic pancreatitis patients, abnormal results in both tests but different degrees of severity in 21%, and totally non-parallel results in 15%. 138 A normal ERCP but abnormal SC test was observed in seven patients, that is, in about 3%.…”
Section: Pancreatic Exocrine Function and Morphological Evidence Of Cmentioning
confidence: 99%